Sistem Informasi Pelelangan Online Pada PT. Balai Lelang Bandung - Novrini Hasti; Irwin Tenrysau (ULTIMA InfoSys, 2017)
PT.Balai Lelang Bandung is a company in Bandung which is located at Ruko Maple Kav. G, Jl. Gn. Batu No. 201, Sukaraja, Cicendo, Bandung - West Java, provides services such as pre-auction, auction, and post auction. The registration process of tender participants is quite convoluted and takes a lot of time in the registration process either in terms of the auction participants or the auctioneer itself. The auction process is very time-consuming bidders themselves, where in conducting the auction, participants are required to attend directly to the auction so many prospective bidders who discontinue their intention to follow the auction process. In this design approach method is prototypemethod, while system development method using Unified Modeling Language (UML). System design tool used to describe the system model such as usecase, scenario diagram, sequence diagram. Index Terms - Information System, Online Auctions, Prototype, UML